Academic Reflections in Times of Crisis: Ten Fading Images of a Fatal Summer - Anatoly Oleksiyenko (Ali Khorsandi Taskoh, 2021)
The scholars of the future may be bemused by the academic tribulations caused by the COVID-19 pandemic. How will temporal distance affect their understanding of this extraordinary time? What records will be available to them in the next decades and centuries, and how will they extract meaning from qualitative research of the past? Analysis of personal reflections will most likely remain subject to the same concerns about data limitations in the future, as is in the present. Yet, it is precisely these human stories that have the potential to tease out the significance of what is likely to be an inflection point in history. The case featured in this paper is a creative rendition produced for a postgraduate class on reflective thinking. It aims to stir the imagination, provoking discussion on what we, as humble learners, need to understand when considering crises and communicating our perceptions and personal experiences across time and cultures. It also exposes the fragility of data and the limitations of temporally-bound interpretations, which insights derived from fragmented data entail.